2016
DOI: 10.1016/j.jstrokecerebrovasdis.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns of Percutaneous Endoscopic Gastrostomy Tube Placement in Acute Stroke: Are the Guidelines Achievable?

Abstract: Objective Our objectives were to evaluate trends in percutaneous endoscopic gastrostomy tube placement rate and timing in acute stroke patients. We hypothesized that non-compliance with clinical practice guidelines for timing of tube placement and an increase in placement has occurred in concordance with a decreased length of hospital stay. Methods We conducted a retrospective observational study of archival hospital billing data from the Florida state inpatient healthcare cost and utilization project databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Similar to findings from other smaller studies, 6 this suggests a mismatch between practice reality and stroke guidelines, which recommend time-limited trials of nasogastric feeding for a period of ≤2 to 3 weeks prior to placing a surgical feeding tube. 7 We found that age was the greatest determinant of early PEG tube placement.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to findings from other smaller studies, 6 this suggests a mismatch between practice reality and stroke guidelines, which recommend time-limited trials of nasogastric feeding for a period of ≤2 to 3 weeks prior to placing a surgical feeding tube. 7 We found that age was the greatest determinant of early PEG tube placement.…”
Section: Discussionsupporting
confidence: 76%
“…Common sequelae of dysphagia are aspiration pneumonia, 1 malnutrition, and dehydration, 2 which can necessitate the placement of a gastrostomy feeding tube, such as a percutaneous endoscopic gastrostomy (PEG) tube. Our research has shown that approximately 5% of all patients hospitalized for stroke receive a PEG tube placement 3 …”
mentioning
confidence: 94%
“…We found that in total only 1.7% of all stroke patients in our study received a PEG tube during their index hospital stay, compared with 5.22% of stroke patients admitted to community hospitals in Florida during 2012 in a previous study. 4 A higher proportion of hemorrhagic than ischemic stroke patients received a PEG tube (4.5% and 1.2%, respectively). This is consistent with our previous findings.…”
Section: Discussionmentioning
confidence: 98%
“…Patients commonly depend on enteral and/or parenteral nutrition because complications from the stroke impact their ability to meet nutrition and hydration needs, for example, as a consequence of dysphagia (swallowing disorders). When there is an anticipated prolonged need for enteral nutrition, percutaneous endoscopic gastrostomy (PEG) tubes are placed in stroke patients, with about 6% of all stroke patients receiving a PEG tube during their acute inpatient hospital stay …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation